The fractal flow conditioner for orifice plate flow meters - Manshoor, B.; Nicolleau, F. C. G. A.; Beck, S.B.M. (Elsevier Ltd., 2011)
The sensitivity of orifice plate flow meters to the quality of the approaching flow continues to be a cause for concern in flow metering. The distortions caused by pipe fittings such as valves, bends, compressors and other devices located upstream of the orifice plate can lead to non-standard velocity profiles and give errors in measurement. The design of orifice plate meters that are independent of the initial flow conditions of the upstream is a major goal in flow metering. Either using a long straight pipe, or a flow conditioner upstream of an orifice plate, usually achieves this goal. The effect of a fractal flow conditioner for both standard and non-standard flow conditions was obtained in experimental work and also using simulations. The measurement of mass flow rate under different conditions and different Reynolds numbers was used to establish a change in discharge coefficient relative to a standard one. The experimental results using the fractal flow conditioner show that the combination of an orifice plate and a fractal flow conditioner is broadly insensitive to upstream disturbances. The simulation results also show that the device can be used as a part of a flow metering package that will considerably reduce installation lengths. Previous work with orifice plates has shown that a combination of flow conditioner and orifice plate was promising. The results of using a combination of the fractal flow conditioner and orifice plate for non-standard flow conditions including swirling flow and asymmetric flow show that this package can preserve the accuracy of metering up to the level required in the Standards.